2017
DOI: 10.1007/s00402-017-2694-y
|View full text |Cite
|
Sign up to set email alerts
|

Is the evaluation of the anterior inferior iliac spine (AIIS) in the AP pelvis possible? Analysis of conventional X-rays and 3D-CT reconstructions

Abstract: Distinct differentiation of the AIIS morphology in the AP pelvis is not possible, but the projection of the AIIS below the anterior acetabular rim represented a hypertrophic AIIS in all cases and should, therefore, be critically investigated for a relevant AIIS impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Figure 1 shows a flowchart illustrating study screening and eligibility assessment. This process identified 23 studies, of which 6 were imaging diagnosis studies, 2 , 4 , 6 , 18 , 22 , 35 9 were prevalence studies, 2 , 5 , 21 , 23 – 25 , 27 , 32 , 33 9 reported outcomes after arthroscopic treatment, ∥ and 9 studies ¶ reported on adverse effects after arthroscopic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 shows a flowchart illustrating study screening and eligibility assessment. This process identified 23 studies, of which 6 were imaging diagnosis studies, 2 , 4 , 6 , 18 , 22 , 35 9 were prevalence studies, 2 , 5 , 21 , 23 – 25 , 27 , 32 , 33 9 reported outcomes after arthroscopic treatment, ∥ and 9 studies ¶ reported on adverse effects after arthroscopic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the 6 studies 2 , 4 , 6 , 18 , 22 , 35 on diagnostic imaging accuracy is shown in Table 1 . Plain radiographs, 3-dimensional reconstructed CT (3D-CT), MRI, and US were used for diagnosis of AIIS impingement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Krueger et al 23 investigated the role of the conventional AP pelvis X-ray in evaluating the projection of the AIIS. They concluded that a precise distinction of the AIIS morphology was not possible in the AP view, and in their cases a distal extension of the AIIS below the anterior acetabular rim was related to type II and III AIIS morphologies in the CT reconstruction.…”
Section: Discussionmentioning
confidence: 99%